Perempuan dalam Melaksanakan Mandat Ilahi Menurut Kejadian 1:27-28 - Wassar, Sarah (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2022)
God gave a divine mandate to humans (women and men) since the beginning of creation is to rule the world (Genesis 1:27). Women and men were created in the image and likeness of God, equal in God's presence, and received the same Divine mandate and carried out the Divine mandate according to God's commands or will. To find out specifically about women in carrying out Divine mandates, this writing is reviewed theologically using qualitative methods, namely literature or literature study. Then it is presented in the form of a theological review description.